2017
DOI: 10.1002/ece3.3543
|View full text |Cite
|
Sign up to set email alerts
|

Effects of macronutrient intake on the lifespan and fecundity of the marula fruit fly, Ceratitis cosyra (Tephritidae): Extreme lifespan in a host specialist

Abstract: In insects, lifespan and reproduction are strongly associated with nutrition. The ratio and amount of nutrients individuals consume affect their life expectancy and reproductive investment. The geometric framework (GF) enables us to explore how animals regulate their intake of multiple nutrients simultaneously and determine how these nutrients interact to affect life‐history traits of interest. Studies using the GF on host‐generalist tephritid flies have highlighted trade‐offs between longevity and reproductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 42 publications
4
31
1
Order By: Relevance
“…The trade‐off between life span and reproduction has been studied extensively in life‐history research (van Noordwijk & de Jong, ). However, there is increasing evidence that the trade‐off between longevity and reproduction arises because these traits are optimized at different P:C ratios (reviewed in Le Couteur et al, ), and that females generally display the greatest reproductive effort at higher P:C ratios (Harrison et al, ; Lee et al, ; Malod et al, ; Solon‐Biet et al, ). In contrast, the effects of macronutrients on the life span cost of reproduction for males are less well defined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The trade‐off between life span and reproduction has been studied extensively in life‐history research (van Noordwijk & de Jong, ). However, there is increasing evidence that the trade‐off between longevity and reproduction arises because these traits are optimized at different P:C ratios (reviewed in Le Couteur et al, ), and that females generally display the greatest reproductive effort at higher P:C ratios (Harrison et al, ; Lee et al, ; Malod et al, ; Solon‐Biet et al, ). In contrast, the effects of macronutrients on the life span cost of reproduction for males are less well defined.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of a multidimensional approach, the Geometric Framework for nutrition, allows the study of interactions between nutrition and trait expression with respect to multiple components in the diet (Simpson & Raubenheimer, ). The Geometric Framework has been used successfully to disentangle the effects of calories and macronutrient balance on life span (Lee et al, ; Solon‐Biet et al, ), and to demonstrate that different ratios of macronutrients, such as protein, carbohydrate and fats, are necessary to maximize different life‐history traits (Bunning et al, ; Malod, Archer, Hunt, Nicolson, & Weldon, ; Solon‐Biet et al, ). For example, in Drosophila melanogaster , females maximize their egg laying rate when consuming food with a protein (P)‐to‐carbohydrate (C) ratio of 1:2, but have the longest life span when given a diet of 1P:16C (Jensen, McClure, Priest, & Hunt, ; Lee et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, an insect may exhibit compensatory feeding and dietary selection (e.g. Abisgold and Simpson, 1987;Fanson et al, 2009;Maklakov et al, 2008;Malod et al, 2017) to achieve a nutrient intake that approaches an optimum defined by its evolved life history strategy. However, it has also been found that restriction of food intake (calories) can lead to 'hormetic' effects, whereby individuals experiencing a mild stress exhibit improved stress resistance and life extension (Le Bourg, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We predicted that stress resistance would be improved by larval development in a nutrient-rich diet, leading to greater body reserves, but consumption of a nutrient-rich diet as an adult would compensate for poor stress resistance associated with a suboptimal larval diet. C. cosyra was chosen as the focus of this study due to availability of data on its adult nutritional intake targets and life history (Malod et al, 2017), its close phylogenetic relationship to other fruit fly species that have been the subject of water balance studies (Weldon et al, 2016(Weldon et al, , 2018 and because it exhibits relatively high desiccation resistance (Weldon et al, 2016). In addition, C. cosyra is an important quarantine pest across sub-Saharan Africa where it affects production of mangoes (Vayssieres et al, 2009;White and Elson-Harris, 1992).…”
Section: Introductionmentioning
confidence: 99%